Synthesis, characterization and release kinetic evaluation of starch nanoparticles loaded with enrofloxacin - Yupanqui Apolinario, Eduardo; Rodriguez Carrillo, Sol Angel; Puente Alvites, Marly Soledad (LACCEI, 2024)
Starch is a natural polysaccharide, versatile and widely available thanks to various native products of Peru, which can be used for the development of new engineering materials. In recent years, starch nanoparticles have been proposed as promising materials for the development of new pharmaceuticals, nutraceuticals or reinforcements (fillers). Hence, the objective of this research is to produce starch nanoparticles from Peruvian potato starches for transport and drug delivery, using enrofloxacin (ENX) as a model drug. Starch nanoparticles were obtained using a flash-nanoprecipitation. Tween®80 was used as a surfactant and sodium tripolyphosphate (STPP) as a crosslinking agent. After the elaboration, all the systems were characterized with various morphological, structural and thermal tests, as well as the encapsulation capacity and drug release of the systems were studied. As a result, the size of the starch nanoparticles was in the range of 10 to 150 nm in diameter, while the sizes of ENX-loaded starch nanoparticles range between 60 and 240 nm. However, no relationship was observed between the variants of potato starch and the characteristics of the starch nanoparticles systems. In all cases, it was shown that the release of ENX is dominated by Fickian diffusive phenomena. In conclusion, the results indicate that starch particles could be considered good alternatives for the preparation of excipients due to the ease of preparation and the possibility of controlling the release kinetics of drugs and active substances.